(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2020)
The publication presents the results of a comparative study of the morphological characteristics of the vegetative and generative organs of plants Tamarix ramosissima Ledeb. and T. odessana Steven ex Bunge. The taxonomic status of T. odessana described by H. Steven from the vicinity of Odessa (Ukraine) is ambiguously interpreted in different floristic reports: it is considered as a separate species or form, it is given the status of a species as part of T. ramosissima, or is not recognized at all. The processing of numerous herbarium specimens (KW) was carried out in order to clarify the question of the possible existence of T. odessana as an independent species. Especially valuable were materials from herbariums M.S. Turchaninov (KW), which presents the only sample collected in Bessarabia, originally identified by V. Besser as "T. tetrandra M.B.", and then redefined as T. odessana. A photocopy of the type sample T. odessana, (Museum Botanicum Univ. (H) Helsinki) was also carefully studied. For comparison, herbarium specimens of T. ramosissima were investigated, in particular, specimen ("No. 718. In arenosis ad lacum Noor-Saisan. Fr. et Augusts. Kar. et Kir. 1840") (KW) collected in the same territory as and type sample T. ramosissima. For greater reliability, other samples of both species were investigated and their initial descriptions were analyzed. According to morphological characters, mainly of generative organs (corolla, petals, sepals, styloid with stigmas) T. odessana differs well from T. ramosissima. The article presents a comparative table with the morphological characteristics of plants of both species and the photos of their vegetative and generative organs, according to which they differ markedly. However, in order to finally resolve the issue of species independence of T. odessana, it would be advisable in the future to draw on molecular biological data that are currently lacking.